The SME sustainability action guide: a six stepsapproach to sustainability implementation among SMEs in Malaysia - Amirrudin, Faizatul Akmam; Mohd Shariff, Balqis (Universiti Teknologi MARA, Terengganu, 2022)
The SME Sustainability Action Guide was launched on 10thof November 2022 to help Malaysian SMEs to adoptsustainability in their business. The UN Global Compact Network Malaysia and Brunei (UNGCMYB) studied thesustainability strategies used by local SMEs and producedthe guide with the support of Taylor's University as aknowledge partner and the Konrad-Adenauer-Stiftung as acooperation partner. The SME Sustainability Action Guidediscusses the value of sustainability to SMEs and the businessbenefits of adopting environmental, social and governance(ESG) practices. Additionally, it provides a detailed, step-by-step implementation strategy towards sustainability.